2014
DOI: 10.1002/ange.201402370
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase Synthesis of Photocaged DNA Resistant against Cleavage by Restriction Endonucleases

Abstract: 5-[(2-Nitrobenzyl)oxymethyl]-2'-deoxyuridine 5'-O-triphosphate was used for polymerase (primer extension or PCR) synthesis of photocaged DNA that is resistant to the cleavage by restriction endonucleases. Photodeprotection of the caged DNA released 5-hydroxymethyluracil-modified nucleic acids, which were fully recognized and cleaved by restriction enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Kruspe and Hahn have recently shown that aptamer stability may not always be the goal, demonstrating that substitution of a DNA aptamer (also against IL-6) with 5-fluoro-dU yields a prodrug that is processed into cytotoxic nucleotides inside target cells [26]. Beyond aptamers, Vanikova and Hocek demonstrate the use of another C5 modification of uracil with light-sensitive chemistry to synthesise replicable double stranded DNA oligonucleotides with photo-activatable nuclease cleavage sites [27].…”
Section: Expanded Functionality and Selection Proceduresmentioning
confidence: 99%
“…Kruspe and Hahn have recently shown that aptamer stability may not always be the goal, demonstrating that substitution of a DNA aptamer (also against IL-6) with 5-fluoro-dU yields a prodrug that is processed into cytotoxic nucleotides inside target cells [26]. Beyond aptamers, Vanikova and Hocek demonstrate the use of another C5 modification of uracil with light-sensitive chemistry to synthesise replicable double stranded DNA oligonucleotides with photo-activatable nuclease cleavage sites [27].…”
Section: Expanded Functionality and Selection Proceduresmentioning
confidence: 99%
“…There have been several studies on the applications and effects of photocaged nucleobases; nonetheless, data regarding the influence of these groups on the activity of restriction enzymes is obscure. Although it has been shown that photocaging DNA with 5‐[(2‐nitrobenzyl(oxymethyl)]‐dU results in transient protection of DNA against cleavage by several REs, photo‐decaging releases 5‐hydroxymethyluracil‐containing DNA, which is susceptible to attack by REs, yet might be invalid for downstream applications . A similar effect has been demonstrated with alternatives to caged DNA, for which (triethylsilyl)ethynyl modification of 7‐deazaadenine, which provides temporary immunity to REs, cannot be removed completely, and leaves DNA with an acetylene residue at position 7 of 7‐deazaadenine .…”
Section: Introductionmentioning
confidence: 97%